2015
DOI: 10.1016/j.sbspro.2015.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Using New Communication and Information Technologies in Preschool Education

Abstract: The research investigated educational activities in terms of educational resources used in preschools. Educational resources were seen as classic teaching tools versus new information technologies teaching tools and resources. From this perspective, the objective of the research has focused on investigating the use of classic and modern educational resources in preschools. The main method used was questionnaire survey. Results obtained show that the vast majority: 96.12% (N=218) uses frequently modern educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In this framework of theoretical considerations, studies fall within the symbolic interaction approach school by emphasizing the action of teachers and students and the conceptualization of their behavior, motivations, beliefs, and the social environment (classroom, school, community, etc.). According to research, most teachers often use traditional teaching aids, and less than half prefer ICT (Lupu & Laurentiu, 2015). In the international literature, it is evident that the usage of ICT is related to teachers' beliefs about technology's role and value in the context of teaching, as well as the pedagogical practices they use (Mama & Hennessy, 2013;Mirzajani et al, 2015), with their readiness (training, motivation, anxiety, and effectiveness) (Demetriadis et al, 2003;Galanouli et al, 2004;Mama & Hennessy, 2013;Mirzajani et al, 2015;Nikolopoulou & Gialamas, 2016;Pelgrum, 2001;Scherer et al, 2014), the barriers they face (heavy workload, management of instructional time, inadequate administrative and technological support, low teacher confidence in using ICT (Butler & Sellbom, 2002;Guha, 2000;Slaouti & Barton, 2007) and the external determinants of learning, such as the social environment (van den Beemt & Diepstraten, 2015).…”
Section: The Teacher In the New Eramentioning
confidence: 99%
“…In this framework of theoretical considerations, studies fall within the symbolic interaction approach school by emphasizing the action of teachers and students and the conceptualization of their behavior, motivations, beliefs, and the social environment (classroom, school, community, etc.). According to research, most teachers often use traditional teaching aids, and less than half prefer ICT (Lupu & Laurentiu, 2015). In the international literature, it is evident that the usage of ICT is related to teachers' beliefs about technology's role and value in the context of teaching, as well as the pedagogical practices they use (Mama & Hennessy, 2013;Mirzajani et al, 2015), with their readiness (training, motivation, anxiety, and effectiveness) (Demetriadis et al, 2003;Galanouli et al, 2004;Mama & Hennessy, 2013;Mirzajani et al, 2015;Nikolopoulou & Gialamas, 2016;Pelgrum, 2001;Scherer et al, 2014), the barriers they face (heavy workload, management of instructional time, inadequate administrative and technological support, low teacher confidence in using ICT (Butler & Sellbom, 2002;Guha, 2000;Slaouti & Barton, 2007) and the external determinants of learning, such as the social environment (van den Beemt & Diepstraten, 2015).…”
Section: The Teacher In the New Eramentioning
confidence: 99%
“…This paper presents a comparative analysis of various ICT application technologies, such as TSLEs, in the education of students of different ages, identifies features of these data technologies, each of them with its own advantages and disadvantages taking into account the baskets of factors proposed by the authoring team. Lupu & Laurentiu (2015) conducted a research among 218 preschool teachers in Romania to identify and analyze educational operations in terms of pedagogical resources used in the learning process. In the course of the study, it was found that classical means (blackboard, chalk/marker) prevailed among the teaching aids used, while ICT was used to a lesser extent.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…This is due to the fact that in Russian practice, urban and rural preschool educational institutions have different methodological, staffing, and technical support. A similar practice of studying preschool institutions has been also applied in foreign studies (Lupu & Laurentiu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The extremely rapid development of technology raises the importance of leaders of higher education institutions, as well as educators teaching public relations, to monitor scientific developments of the profession, market trends, and in particular, the needs of employers who will in the future employ recently educated personnel . The results in article were shown that teacher use both classic and information technology as educational resources, and are aware of their benefits and limits. According to the results in article the key advantage of flexibility by using of information technology is supported, though with little evidence for effect on depth of learning.…”
Section: Introductionmentioning
confidence: 99%